Gary Hall Jr's Full Stroke at 35 m of His Leg of the 4 x 100 m Freestyle Relay Gold Medal Race at the 1998 Perth World Championships - Rushall, B. S.
Video pictures (14 frames) and the appropriate technical/ biomechanical explanations for Gary Hall Jr's Full Stroke at 35 m of His Leg of the 4 x 100 m Freestyle Relay Gold Medal Race at the 1998 Perth World Championships. Gary Hall Jr's stroke is asymmetrical, the left arm exhibiting a totally different movement pattern to that of the right arm. The left arm pull also appears to contain more critical movement "errors" than the right. Improvement might be possible if the forms of each arm pull were more similar and force production better balanced. One can only speculate why the swimmer is not swimming as well as in the past. Certainly, the left arm pulling motion and the carriage of the head, which disrupts streamline, could contribute to performance decrement.